Precision Polymer Design in Microstructured Flow Reactors: Improved Control and First Upscale at Once - Junkers, Thomas (Macromolecular chemistry and physics, 2017)
Continuous flow synthesis techniques have in recent years conquered laboratory scale synthesis, yet within the field of precision polymer synthesis its use is still not fully established despite the large advantages that can be gained from switching from classical batch‐wise chemistry to flow chemistry, often already by using relatively simple chip‐based or cheap tubular micro‐ and mesoscaled reactors. Translating a polymerization from batch to continuous flow marks not only a mere change in reactor engineering, but also leads to numerous advantages in the polymerization with respect to kinetics of processes and especially product quality. In flow, polymerizations are not only speed up, they also provide materials with better dispersities and higher chain end fidelities when conditions are chosen accordingly. The underpinning effects causing these improvements are demonstrated and discussed. Further, also information on required laboratory equipment and recent developments in online reaction monitoring are highlighted to give newcomers to the field an idea about the potential of continuous flow polymerization. The advantages of using microreactors for precision polymer synthesis are highlighted and compared to classical polymerization methodologies, demonstrating that continuous flow reactors do not only lead to improved kinetics of processes, but also to a higher quality of the residual polymers. The field of continuous flow polymerization is still at its start, but the potential is eminent and some future developments are discussed.